EVOLUTION OF WOMEN IN INDIAN CINEMA : A COMPARATIVE ANALYSIS OF DECADES THROUGH 10 ICONIC FILMS - Singh, Priyanka; Kumari, Pallavi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian cinema has long been a mirror reflecting societal norms and cultural shifts, with the portrayal of women evolving significantly over the years. This research explores the changing roles of women in Indian cinema over five decades, delving into the nuanced portrayals through a comparative analysis of ten influential films. Selected films, two from each decade (80s, 90s, 2000s, 2010s, and 2020s), serve as windows into the evolving dynamics of female characters and their representation. Through a critical examination of these cinematic masterpieces, this study aims to unravel the multifaceted dimensions of female characters, investigating how their roles, agency, and representations have metamorphosed over time. By examining how women are depicted in various contexts, the research sheds light on the evolving narratives and societal perceptions captured by Indian filmmakers, contributing to a deeper understanding of the shifting cultural landscape through the lens of cinema.